QUESTIONING AND ANSWERING: A LEARNING TECHNIQUE TO IMPROVE COMMUNICATION SKILL AND LEARNING OUTCOME IN THE PRIMARY SCHOOL - Asmanidar Asmanidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
Communication skills are the ability to express ideas both verbally and non-verbally. Learning outcomes are the level of acquisition of student knowledge related to the development of competencies. Both of these can be improved in the classroom by using Questioning and Answering techniques. The purpose of the study is to improve communication skills and student learning outcomes in class IV SDN 006 Langgini. The study design used a Classroom Action Research design which consisted of four stages: planning, action, observation and reflection. The research subjects were 29 students in class IV SDN 006 Langgini. The instrument for measuring communication skills used observation sheets while learning outcomes were assessed by providing tests. Data were analyzed descriptively and quantitatively. The results showed communication skills in first cycle was 63.22 and in second cycle amounted to 73.99 which meant an increase from first cycle to second cycle. Learning outcomes also increased by 74.21 in first cycle and 89.66 in second cycle. Thus it can be concluded that the application of techniques Questioning and Answering can improve communication skills and learning outcomes of fourth grade students of SDN 006 Langgini in semester 2019/2020.